Bidentate Phosphanyl‐ and Arsanylboranes. Issue 2 (11th December 2018) - Hegen, Oliver; Braese, Jens; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: A new class of neutral bidentate ligands with pnictogenyl‐functional sites has been obtained. The reaction of tmeda⋅(BH2 I)2 (1, tmeda=tetramethylethylendiamine) with different phosphanides yields the corresponding bidentate phosphanylboranes tmeda⋅(BH2 PH2 )2 (2 a ), tmeda⋅(BH2 PPh2 )2 (2 b ), and tmeda⋅(BH2 t BuPH)2 (2 c ). This reaction strategy could be further extended to synthesize the first bidentate arsanylborane tmeda⋅(BH2 AsPh2 )2 (3 ). Depending on the substituents on the phosphorus, these compounds form different Au I complexes, to build either polymeric tmeda⋅(BH2 PH2 AuCl)2 (4 a ), or monomeric tmeda⋅(BH2 PPh2 AuCl)2 (4 b ) products. These compounds form also neutral oligomeric group 13/15 chain‐like molecules by coordination to a boron moiety such as tmeda⋅(BH2 PH2 BH3 )2 (5 a ) and tmeda⋅(BH2 AsPh2 BH3 )2 (5 b ). DFT calculations provide insight into the differences between the syntheses of mono‐ and bidentate pnictogenylboranes. Abstract : Value pack: two for the price of one ! By using a bidentate Lewis base, a new class of ligands of bidentate pnictogenylboranes were synthesized. These compounds were used for the formation of novel oligomeric boron‐pnictogen compounds and of coordination compounds of Au I . Depending on the substituents on the phosphorus atom, either monomeric or polymeric compounds are formed in the solid state.